Assessment of predictive dermal exposure to chemicals in the work environment - Agnieszka Jankowska; Sławomir Czerczak; Małgorzata Kupczewska-Dobecka (Nofer Institute of Occupational Medicine, 2017)
Assessment of dermal exposure to chemicals in the work environment is problematic, mainly as a result of the lack of measurement data on occupational exposure to chemicals. Due to common prevalence of occupational skin exposure and its health consequences it is necessary to look for efficient solutions allowing for reliable exposure assessment. The aim of the study is to present predictive models used to assess non-measured dermal exposure, as well as to acquaint Polish users with the principles of the selected model functioning. This paper presents examples of models to assist the employer in the the assessment of occupational exposure associated with the skin contact with chemicals, developed in European Union (EU) countries, as well as in countries outside the EU. Based on the literature data dermal exposure models EASE (Estimation and Assessment of Substance Exposure), COSHH Essentials (Control of Substances Hazardous to Health Regulations), DREAM (Dermal Exposure Assessment Method), Stoffenmanager , ECETOC TRA (European Centre for Ecotoxicology and Toxicology of Chemicals Targeted Risk Assessment), MEASE (Metal's EASE), PHED (Pesticide Handlers Exposure Database), DERM (Dermal Exposure Ranking Method) and RISKOFDERM (Risk Assessment of Occupational Dermal Exposure to Chemicals) were briefly described. Moreover the characteristics of RISKOFDERM, guidelines for its use, information on input and output data were further detailed. Problem of full work shift dermal exposure assessment is described. An example of exposure assessment using RISKOFDERM and effectiveness evaluation to date were also presented. When no measurements are available, RISKOFDERM allows dermal exposure assessment and thus can improve the risk assessment quality and effectiveness of dermal risk management. Med Pr 2017;68(4):557-569